THE POTENTIAL BIODEGRADATION HYDROCARBONS OF PETROLEUM SLUDGE WASTE BY CELL BIOMASS SPONGE Callysppongia sp. - Ismail Marzuki; Alfian Noor; Nursiah La Nafie (Marina Chimica Acta, 2015)
The toxicity of petroleum sludge is a serious threat to marine life. Necessary concrete stepspetroleum contamination reduction through a search of potential marine materials degradetoxic components hydrocarbons. The sponge is one potential material reducing toxicproperties of petroleum contamination. The research objective was to determine thepotential Callyspongia sp sponge against the degradation of petroleum hydrocarbonsludge. Four variations of treatment used to determine the potential of sponge biomass,namely: the treatment I, II, III and IV. Indicators degradation is the formation of gas, thesmell fermentation, pH changes and increase in the absorbance of the suspension of mediadegradation. The level degradation each treatment is determined gravimetric method andthe known hydrocarbon component changes by using GC-MS. Unidentified gas, the smellof fermentation and changes in media of pH on average degradation occurs on the 15 daysof contact for all treatments. Data showed degradation occurs absorbance maximum at 20-25 days to contact. The highest degradation rates indicated by IV treatment (26.93 %), III(24.84 %), II (22.59 %), and I: (18.20 %). Found 20 kinds of components in the wastesludge aliphatic petroleum to form a homologous series nC10-nC30, and two aromaticcomponents, namely the 2.7-dimethyl naphthalene and 1.4-dimethyl azulene. Callyspongiasp sponge biomass concluded at the highest IV treatment degrading aliphatichydrocarbons, then treatment III, II and I, while the aromatic components are not degradedby biomass Callyspongia sp sponge at all treatments.